Rhaebo haematiticus (litter toad) and Craugastor fitzingeri (Fitzinger's rain frog) reproductive behavior - Stynoski, Jennifer Lynn (2013)
C. fitzingeri was observed in amplexus with a large female R. haematiticus at Sarapiquí, Costa Rica